Socio-educational intervention for nursing practice: use of the dignified treatment indicator - Díaz-Oviedo, Aracely (Universidad de Sonora, 2020)
Introduction: The health care of the population is one of the commitments of the nursingprofessional in the institutions dedicated to cover it, so it is important to identify failures, successes and establish strategies to offer a humanized care. Objective: To implement a socio-educational intervention for the use of the indicator dignified treatment in nursing professionals for the care of the hospitalized patient. Method: A socio-educational intervention was carried out as a pre-experimental study with pretest-posttest conducted from February to March 2017 in a public hospital in San Luis Potosí, Mexico to 37 hospitalization nurses, which strengthens the humanized care of the patient and the patients were evaluated. Nursing knowledge after implementing the program contrasting the pre and post which was assessed using a pre-experimental study with pretest-posttest and the parametric T Student test. Results: When implementing the program with the implementation of the socio-educational intervention for nurses, an increase of 10% to 40% was obtained in each of the dimensions and comparing the means of the before and after there was a significant difference of the Averages obtained. Conclusions: The socioeducational intervention increases the knowledge about the good use of the Worthy Treatment indicator for the improvement in patient care, in nurses as the center of the intervention.